2003
DOI: 10.1074/jbc.m307332200
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Sp1 Activity through Modulation of O-Glycosylation by Treatment with a Low Glucose Mimetic, 2-Deoxyglucose

Abstract: 2-Deoxyglucose (2-DG), a nonmetabolizable glucose analogue, blocks glycolysis at the phosphohexose isomerase step and has been frequently used as a glucose starvation mimetic in studies of a wide variety of physiological dysfuctions. However, the effect of 2-DG on protein glycosylation and related signal pathways has not been investigated in depth. In HeLa, an HPV18-positive cervical carcinoma line, 2-DG treatment downregulates human papillomavirus early gene transcription. This down-regulation was also achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 62 publications
4
59
0
Order By: Relevance
“…Fasting, glucose starvation and hypoxia can cause degradation of Sp1 or downregulation of the DNA binding activity of Sp1 via post-translational modifications such as O-linked glycosylation at serine/threonine residues. [22][23][24] One possibility is that PanK1 expression is regulated by Sp1 during normal physiological conditions. However, in the face of energy deprivation, Sp1 activity diminishes to conserve nutrients, while p53 is activated in response to metabolic stress to maintain the expression of PanK1.…”
Section: Discussionmentioning
confidence: 99%
“…Fasting, glucose starvation and hypoxia can cause degradation of Sp1 or downregulation of the DNA binding activity of Sp1 via post-translational modifications such as O-linked glycosylation at serine/threonine residues. [22][23][24] One possibility is that PanK1 expression is regulated by Sp1 during normal physiological conditions. However, in the face of energy deprivation, Sp1 activity diminishes to conserve nutrients, while p53 is activated in response to metabolic stress to maintain the expression of PanK1.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Mcl-1 has been demonstrated in AML cells, and removal of Mcl-1, but not other member of the Bcl-2 family, including Bcl-xL, Bcl-2, or Bcl-w, induced leukemic cell death, setting Mcl-1 as a valuable therapeutic target in AML (27,28). Independently of its effect on glycolysis, 2-DG can also affect protein glycosylation by interfering with N-linked glycosylation, leading to accumulation of misfolded proteins and an ER stress response (29)(30)(31)(32). This mechanism can be alleviated by D-mannose supplementation without affecting the inhibition of glycolysis induced by 2-DG.…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of RL-2 to the OGlcNAcylated proteins in whole cell extract has been demonstrated in a previous study by the increased intensity of the bands from the cells treated with streptozotocin, an inhibitor of OGlcNAcase (Kang et al, 2003). Upon the treatment of nicotinamide, O-GlcNAcylation level of total cellular proteins was rapidly and dramatically reduced in parallel to the change of Sp1 protein level ( Figure 3A).…”
Section: Nicotinamide-induced Downregulation In O-glcnacylation Of Cementioning
confidence: 76%
“…The decrease in the level of the O-GlcNAcylated proteins showed a time-course profile that is identical to that of Sp1 ( Figure 3B, NAM). Furthermore, the nicotinamide-induced decrease in both the O-GlcNAcylation level of cellular proteins and the Sp1 level was blocked by co-treatment of 10 mM glucosamine, a key precursor and stimulator of protein O-GlcNAcylation (Konrad et al, 2000) or 45 mM 2-deoxyglucose, a glucose-derivative that has been shown to inhibit protein de-GlcNAcylation (Kang et al, 2003) (Figure 3B, NAM + GA and NAM + 2-DG). This strongly suggests a possibility of a direct interference by nicotinamide in protein O-GlcNAcylation.…”
Section: Nicotinamide-induced Downregulation In O-glcnacylation Of Cementioning
confidence: 99%